Securitization: A Low-Cost Sweetener for Lemons - Claire A. Hill (Washington University Law Quarterly, 1996)
Part II provides an overview of securitization transactions. Part III describes the terms of securitization transactions. These two sections are for readers desiring an understanding of the transaction structure and its complexities. Part IV contains the main argument of this Article: it explains the source of securitization's benefits using a Modigliani and Miller framework. Part V offers concluding remarks.
Keywords: Securities